Exploring Biofarma’s Readiness Factors Advancing From Integrated Systems To Predictive Analytics And Real-Time Monitoring - Arief, Neneng Nurlaela; Syahril Maulana, Rijal (Riviera Publishing, 2025)
This study investigates Biofarma’s readiness to Pharma 4.0 technologies adoption to implement predictive analytics, Artificial Intelligence, and the Internet of Things by assessing key factors. The research using quantitative surveys to explore the digital transformation landscape within the company. This study is using Exploratory Factor Analysis and Confirmatory Factor Analysis to reveal latent constructs influencing readiness. The findings show five main factors motivating readiness: perceived utility of digital tools, workforce digital competence, technology infrastructure readiness, stakeholder alignment, and perceived ease of use. These elements confirmed the structural integrity of the survey tool by matching it with Pharma 4.0 frameworks. The results of this study confirm five main factors influencing Bio Farma’s readiness to advance to Level 4 in the Pharma 4.0 framework, with one factor identified as the most influential.